Draumkvedet, Tony Valberg Musikkteateret mellom drømmen og hendelsene - Valberg, Tony (Peripeti, 2021)
Den norske musiker og forsker Tony Valberg har mange års erfaring med koncerter og musikdramatik for børn. Med udgangspunkt i forestillingen Draumkvedet, som blev spillet langt over 200 gange i Norge og Sverige, præsenterer han en lang række (musik)dramaturgiske overvejelser og fører læseren ind i den relationelle æstetik og dens forudsætninger i avantgardemusikken og -teatret siden 1950erne. Her tematiseres det interaktive aspekt, børnenes aktive performative medvirken, som et afgørende nyt element i det 21. århundredes musikteater Under modern conditions, art music has shown a particular need to establish itself as a discipline independent of the other arts, as “pure” instrumental music. However, musical entrepreneurs such as John Cage have delved into aesthetics and performative practices that exceed the boundaries between music and the other arts. A production like the Norwegian childrens’ music theatre play Draumkvedet (he Dream Song) exemplifies music’s function in music theatre when it 1) unfolds like a traditionally formed narrative and 2) unfolds like a non-linear event that establishes a relational presence. As such, Draumkvedet suggests how music may play a specific role in the musical theatre whether approached as a “work of art” or an “event”.